Structure solution of DNA‐binding proteins and complexes with ARCIMBOLDO libraries. (1st June 2014) - Pröpper, Kevin; Meindl, Kathrin; Sammito, Massimo; Dittrich, Birger; Sheldrick, George M.; Pohl, Ehmke; Usón, Isabel
<x xml:space="preserve">Abstract</x> Protein–DNA interactions play a major role in all aspects of genetic activity within an organism, such as transcription, packaging, rearrangement, replication and repair. The molecular detail of protein–DNA interactions can be best visualized through crystallography, and structures emphasizing insight into the principles of binding and base‐sequence recognition are essential to understanding the subtleties of the underlying mechanisms. An increasing number of high‐quality DNA‐binding protein structure determinations have been witnessed despite the fact that the crystallographic particularities of nucleic acids tend to pose specific challenges to methods primarily developed for proteins. Crystallographic structure solution of protein–DNA complexes therefore remains a challenging area that is in need of optimized experimental and computational methods. The potential of the structure‐solution program ARCIMBOLDO for the solution of protein–DNA complexes has therefore been assessed. The method is based on the combination of locating small, very accurate fragments using the program Phaser and density modification with the program SHELXE. Whereas for typical proteins main‐chain α‐helices provide the ideal, almost ubiquitous, small fragments to start searches, in the case of DNA complexes the binding motifs and DNA double helix constitute suitable search fragments. The aim of this work is to provide an effective library of search fragments as well as to determine the optimal ARCIMBOLDO strategy for the solution of this class of structures.